Fossil Fruits of Ceratophyllum from the Upper Eocene and Miocene of South China - Shenglan Xu; Hanzhang Song; Helanlin Xiang; Weiqiu Liu; Cheng Quan; Jianhua Jin (Biology, 2022)
Ceratophyllum L. is a cosmopolitan genus of perennial aquatic herbs that occur in quiet freshwaters. Fossils of this genus have been widely reported from the Northern Hemisphere, most of them occurring in the temperate zone. Here, we describe two species of fossil fruits discovered from subtropical areas of China. The fossil fruit discovered from the upper Eocene Huangniuling Formation of the Maoming Basin is designated as C. cf. muricatum Chamisso, and fruits discovered from the Miocene Erzitang Formation of the Guiping Basin are assigned to the extant species C. demersum L. The discovery of these two fossil species indicates that Ceratophyllum had spread to South China by the late Eocene and their distribution expanded in subtropical China during the Miocene.